PEMANFAATAN NaHCO3 DALAM PEMBUATAN TEMPE BERBAHAN BAKU BIJI NANGKA DAN BIJI SAGA - Randa, Agustian; Yusmarini, Yusmarini; Zalfiatri, Yelmira (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purposes of the study was to obtain the best tempeh from utilization of NaHCO3 in making tempeh with raw material jackfruit seeds and saga seeds using the SNI quality standards. The research was conducted experimentally using completely randomized design (CRD) with four treatments and four repetitions, followed by DNMRT test at 5% level. The treatment in this study were SS1 (saga seeds soaked in water for 24 hours and soaked in hot water ±60ºC for 10 minutes), SS2 (saga seeds soaked in a solution of NaHCO3 2,5% for 24 hours and soaked in hot water ±60ºC for 10 minutes), SS3 (saga seeds soaked in a solution of NaHCO3 2,5% for 24 hours and soaked in hot solution of NaHCO3 2,5% ±60ºC for 10 minutes) and SS4 (saga seeds soaked in water for 24 hours and soaked in hot solution of NaHCO3 2,5% ±60ºC for 10 minutes). Parameters observed were the moisture, ash, fat, protein and sensory evaluation after and before frying. Results of the analysis of variance showed the soaking time saga seeds with a solution of NaHCO3 2,5% significantly affected all parameters. The results of the study found that the best treatment was SS4 with a value of 61,35% moisture content, 1,12% ash, 5,30% fat, 22,75% protein and an overall assessment of sensory preferred by panelists. Keywords: NaHCO3, tempeh, jackfruit seeds, saga seeds.